Topic application of meloxicam-loaded polymeric nanocapsules as a technological alternative for treatment of the atopic dermatitis in mice - Weber, Douglas Mroginski; Voss, Guilherme Teixeira; Oliveira, Renata Leivas de; Fonseca, Caren A.R. da; Paltian, Jaini; Rodriguez, K. C; Ianiski, Francine Rodrigues; Vaucher, R. A; Luchese, Cristiane; Wilhelm, Ethel Antunes (Journal of Applied Biomedicine, 2018)
This study investigated the effect of the topical treatment with meloxicam-loaded nanocapsules (M-NC) on symptoms, inflammatory response and oxidative parameters in an atopic dermatitis (AD) model in BALB/c mice. 2,4-Dinitrochlorobenzene (DNCB) was applied to the dorsal skin on days 1–3 for sensitization. Mice were challenged with DNCB on the ear (on days 14–29) and dorsal skin (on days 14, 17, 20, 23, 26, and 29). Treatments with blank nanocapsules (B-NC), free meloxicam (M-F) or M-NC were applied to the backs of the mice from days 14 to 29. On the day 30, skin severity scores and scratching behaviour were determined. After that, ears and dorsal skin were removed for determination of inflammatory parameters (edema and myeloperoxidase (MPO) activity) and oxidative parameters (thiobarbituric acid reactive species (TBARS) and non-protein thiol (NPSH) levels), respectively. DNCB increased the severity of skin lesions, scratching behaviour, edema and MPO activity of ears and dorsal skin TBARS levels. M-NC reversed skin severity scores, scratching behaviour and inflammatory response induced by DNCB. B-NC and M-F did not have effect in this model. In summary, meloxicam carried by polymeric nanocapsules reversed inflammatory response and ameliorated symptoms in an AD model.
Keywords: meloxikam; Animals; způsoby aplikace léků; Female; lékové formy; Dermatitis, Atopic; výsledek terapie; ženské pohlaví; Dosage Forms; Nanocapsules; Drug Carriers; aplikace kožní; Meloxicam; Administration, Cutaneous; Treatment Outcome; atopická dermatitida; Mice, Inbred BALB C; modely nemocí na zvířatech; myši inbrední BALB C; nanokapsle; Disease Models, Animal; nosiče léků; zvířata; Drug Administration Routes